Prevalence of zoonotic and non-zoonotic Rickettsia in horses: A systematic review and meta-analysis - Bonilla-Aldana, D. Katterine (2023)
In a broad sense, Rickettsiae are a group of microorganisms that can be transmitted mechanically or biologically to animals and humans. Rickettsioses are associated with hematic manifestations. Its prevalence in humans, dogs and other animals has been widely explored, but not in equine species. To determine the prevalence of Rickettsia infection in horses. A systematic review of the literature was carried out in five databases for the proportion of horses infected with Rickettsia, defined by molecular and immunological techniques. A meta-analysis was performed using a random-effects model to calculate the pooled prevalence and 95% confidence intervals (CI). The Cochran's Q test and the I2 statistic were used to assess the between-study-heterogeneity. The pooled prevalence of Rickettsia in equines was 37.0% (95% CI: 26.0%-47.0%), with significant heterogeneity among studies (I2 = 98.12%). In the subgroup analysis, the prevalence of Rickettsia in horses was found to be 24.0% (95%CI: 10.0%-41.0%) for IFI, 47.0% (95%CI: 30.0%-64.0%) for IFA, 14.0% (95%CI: 11.0%-17.0%) for IFAT and 39.0% (95%CI: 0.0%-95.0%) for PCR. There was a high prevalence of Rickettsia among horses, with some of the species being zoonotic, with their corresponding implications for humans, which increasingly are in close contact with equines, particularly horses and their ticks, posing a risk for spillover and transmission.